Spectrum of dengue morbidity in pregnancy and its impact on maternal and perinatal outcome - G., Anuradha; M. R., Sandya; George, Shirley (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Dengue is a vector borne viral infection with seasonal outbreaks every year. The spectrum varies from just a febrile morbidity to the severe form of dengue shock syndrome (DSS). The objective of the present study was to study the influence of dengue fever on pregnancy and to analyze the maternal and perinatal outcome. Methods: Thirty-six pregnant women beyond 28weeks of gestation who tested positive for dengue infection were retrospectively analyzed during a 5year study period (Jan 2014-Dec 2018). The study was conducted in the Department of OBGYN St John’s Medical College Hospital, Bangalore. Thirty-three of these patients delivered at St John’s and there were three postpartum referral cases. The necessary data was obtained by patient record review. The data was analyzed using SPSS and the results were expressed as Mean±SD and percentages. Results: Out of 36 women analyzed the mean age was found to be 23.93±4.5 years. Majority were primigravidae (58.3%). The most common clinical manifestation was fever seen in 47.2%. Twenty five percent of patients had platelet count of <20,000 on admission. Overall 66% of the patients required transfusion. Nearly fifty three percent of the patients had vaginal delivery. There were 4 maternal mortalities (11.1%) and 2 perinatal mortalities (5.5%) both were still births in the present study. Conclusions: Dengue infection in pregnancy was associated with increased maternal and perinatal morbidity as well as mortality. The severity of the infection has direct impact on the outcome. Hence early diagnosis and prompt management in a tertiary care centre, with multidisciplinary approach improves the outcome and minimizes the complications.